Vorinostat in patients with advanced malignant pleural mesothelioma who have progressed on previous chemotherapy (VANTAGE-014): a phase 3, double-blind, randomised, placebo-controlled trial. Issue 4 (April 2015) - Krug, Lee M; Kindler, Hedy L; Calvert, Hilary; Manegold, Christian; Tsao, Anne S; Fennell, Dean; Öhman, Ronny; Plummer, Ruth; Eberhardt, Wilfried E E; Fukuoka, Kazuya; Gaafar, Rabab M; Lafitte, Jean-Jacques; et al.
Summary: Background: Vorinostat is a histone deacetylase inhibitor that changes gene expression and protein activity. On the basis of the clinical benefit reported in patients with malignant pleural mesothelioma treated in a phase 1 study of vorinostat, we designed this phase 3 trial to investigate whether vorinostat given as a second-line or third-line therapy improved patients' overall survival. Methods: This double-blind, randomised, placebo-controlled trial was done in 90 international centres. Patients with measurable advanced malignant pleural mesothelioma and disease progression after one or two previous systemic regimens were eligible. After stratification for Karnofsky performance status, histology, and number of previous chemotherapy regimens, patients were randomly assigned (1:1) by use of an interactive voice response system with a block size of four to either treatment with vorinostat or placebo. Patients received oral vorinostat 300 mg (or matching placebo) twice daily on days 1, 2, 3, 8, 9, 10, 15, 16, and 17 of a 21-day cycle. The primary endpoints were overall survival and safety and tolerability of vorinostat. The primary efficacy comparison was done in the intention-to-treat population, and safety and tolerability was assessed in the treated population. This trial is registered with ClinicalTrials.gov, number NCT00128102 . Findings: From July 12, 2005, to Feb 14, 2011, 661 patients were enrolled and randomly assigned to receive either vorinostat (n=329) or placebo (n=332) and included in the intention-to-treat analysis. Median overall survival for vorinostat was 30·7 weeks (95% CI 26·7–36·1) versus 27·1 weeks (23·1–31·9) for placebo (hazard ratio 0·98, 95% CI 0·83–1·17, p=0·86). The most common grade 3 or worse adverse events for patients treated with vorinostat were fatigue or malaise (51 [16%] patients in the vorinostat group vs 25 [8%] in the placebo group]) and dyspnoea (35 [11%] vs 45 [14%]). Interpretation: In this randomised trial, vorinostat given as a second-line or third-line therapy did not improve overall survival and cannot be recommended as a therapy for patients with advanced malignant pleural mesothelioma. Funding: Merck & Co, Inc.